IoT and Solar Powered Storage System for Agricultural Product Quality Enhancement - Suhra, Aminatus; Rohmayati, Nita Selvia; Junaidi, Imam; Sari, Cindy Yulia Kartika (Research Horizon, 2025)
Postharvest losses remain a critical issue for corn farmers in Sumenep Regency, particularly in Lenteng Timur Village, where traditional storage methods fail to maintain product quality. This study aimed to design and develop an Internet of Things (IoT)-based agricultural storage system powered by renewable energy to enhance product quality, extend shelf life, and reduce farmer losses. The research employed a Research and Development (R&D) approach adapted from the Borg and Gall model, limited to six stages: problem identification, planning, prototype development, preliminary testing, revision, and main field testing. The system integrates DHT22 and MQ-135 sensors with an ESP32 microcontroller and a 200–300 Wp solar photovoltaic system. Field trials demonstrated that the IoT monitoring application provided real-time temperature, humidity, and gas concentration data with <2% deviation. The solar energy system generated 0.8–1.0 kWh/day, sufficient for continuous operation. Corn stored for 30 days in the IoT system exhibited 2.8% weight loss and 13–14% moisture content, compared to 7.4% weight loss and 16–18% moisture in traditional storage. User evaluation indicated high acceptance, with 90% of farmers reporting easier monitoring and 80% finding the system easy to use. These results suggest that integrating IoT and renewable energy in storage systems can effectively reduce postharvest losses, maintain crop quality, and promote sustainable agricultural practices. Further refinements are needed to enhance user-friendliness and backup energy capacity for broader implementation.